Preparation and antibacterial activity of p-Anisyl ethyl fumarate and ethyl n-phenyl fumaramate - ., Jumina; Zulkarnain, Abdul Karim; Mulyono, Panut (Indonesian Journal of Pharmacy, 2005)
In order to generate potent C-9154 antibiotic derivatives, it has been conducted the synthesis and antibacterial activity evaluation of p-anisyl ethyl fumarate and ethyl N-phenyl fumaramate. These target molecules were chosen as the former would be a para-methoxy substituted C-9154 derivative, whereas the latter would be an example of unsubstituted C-9154 derivative bearing an amido-ester fumaric side chain.p-Anisyl ethyl fumarate was synthesized from p-anisaldehyde by reduction with NaBH4, condensation of p-anisyl alcohol with maleic anhydride, and esterification of the resulting p-anisyl maleic acid with ethanol in the presence of benzenesulfonic acid as the catalyst. These reactions gave satisfactorily yields (55-81 %) in all steps involved. In the case of ethyl Nphenyl fumaramate, this molecule was synthesized in 84 % yield through condensation of aniline with maleic anhydride, followed by esterification with ethanol in the presence of concentrated sulfuric acid.The antibacterial activity test showed that the minimum inhibition concentration (MIC) of p-anisyl ethyl fumarate and ethyl N-phenyl fumaramate towards Staphyllococcus aureus were 15 and 25 μg/mL. Interestingly, the MIC values of these two compounds towards Eschericia coliwere also 15 and 25 μg/mL respectively. Thus, the data showed that the two C-9154 derivatives obtained are sufficiently potent and possess antibacterial activities which are comparable to the antibacterial activity of C-9154 itself towards Staphyllococcus aureus (12.5 – 37.5 μg/mL) and Eschericia coli (25 – 50 μg/mL).Key words: synthesis, antibacterial activity, fumarate and fumaramate.